2020
DOI: 10.1194/jlr.ra120001006
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of essential isoprenoids and ER stress induction following acute liver-specific deletion of HMG-CoA reductase

Abstract: HMG-CoA Reductase (Hmgcr) is the rate-limiting enzyme in the mevalonate pathway and is inhibited by statins. In addition to cholesterol, Hmgcr activity is also required for synthesizing non-sterol isoprenoids, such as dolichol, ubiquinone, farnesylated and geranylgeranylated proteins. Here, we investigated the effects of Hmgcr inhibition on non-sterol isoprenoids in the liver. We have generated new genetic models to acutely delete genes in the mevalonate pathway in the liver using AAV-mediated delivery of Cre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Several studies using tissue-specific Hmgcr KO mice have shown that the MVA pathway is an important physiological regulator of cell survival by producing non-sterol isoprenoid intermediates in various cells. 15 , 58 , 68 , 69 However, the mechanism by which the MVA pathway affects mature brown adipocytes remains unclear. In this study, we showed that disruption of the MVA pathway causes programmed cell death owing to a lack of GGPP synthesis in mature brown adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using tissue-specific Hmgcr KO mice have shown that the MVA pathway is an important physiological regulator of cell survival by producing non-sterol isoprenoid intermediates in various cells. 15 , 58 , 68 , 69 However, the mechanism by which the MVA pathway affects mature brown adipocytes remains unclear. In this study, we showed that disruption of the MVA pathway causes programmed cell death owing to a lack of GGPP synthesis in mature brown adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“… 13 However, statins also exhibit several adverse effects, such as rhabdomyolysis, liver damage, and an increased risk of T2D, which appear to be primarily mediated by the suppression of isoprenoid biosynthesis. 14 Although the mechanisms underlying the adverse effects on skeletal muscle and the liver have been gradually clarified by tissue-specific inhibition of the MVA pathway in mice, 15 , 16 , 17 the mechanisms underlying the statin-mediated increased risk of T2D remain unclear. A recent study showed an inverse correlation between statin use and active BAT in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we recently demonstrated that our AAV-CRISPR system is liver restricted, resulting in no Cas9 activity in extra-hepatic tissues. 32 Targeted integration in post-mitotic tissues, such as the adult liver, is limited by the very low rate of HDR-mediated repair. We determined the targeting frequency with three approaches: (1) ddPCR, (2) immunohistochemistry, and (3) co-expression of apoA1-2A and the transgenic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we recently demonstrated that our AAV-CRISPR system is liver restricted, resulting in no Cas9 activity in extra-hepatic tissues. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Paraffin embedding, sectioning, and antibody staining were performed by the Texas Digestive Diseases Morphology core as previously described. 54 Slides were imaged at Â10 magnification on a Nikon Ci-L bright-field microscope at the Integrated Microscopy Core (Baylor College of Medicine). Ki67-and TUNEL-positive cell quantification was performed by manual count, and nuclei were quantified by ImageJ (https:// imagej.nih.gov).…”
Section: Histologymentioning
confidence: 99%